Inhibition of Helicobacter pylori growth in vitro by Bulgarian propolis: preliminary report - Boyanova, Lyudmila; Derejian, Sirigan; Koumanova, Radka; Katsarov, Nikolai; Gergova, Galina; Mitov, Ivan; Nikolov, Rossen; Krastev, Zacharii (Journal of Medical Microbiology, 2003)
Bee glue (propolis) possesses antimicrobial, anti-inflammatory, anaesthetic and immunostimulating activities. The aim of the study was to evaluate the inhibitory effect of Bulgarian propolis on Helicobacter pylori growth in vitro. Activity of 30 % ethanolic extract of propolis (EEP) against 38 clinical isolates of H. pylori was evaluated by using the agar-well diffusion method. Ethanol was used as a control. In addition, the effect of propolis on the growth of 26 H. pylori and 18 Campylobacter strains was tested by the disc diffusion method. Mean diameters of H. pylori growth inhibition by the agar-well diffusion method, using 30, 60 or 90 μl EEP or 30 μl ethanol per well, were 17.8, 21.2, 28.2 and 8.5 mm, respectively. EEP was significantly more active than ethanol against H. pylori (P < 0.001). The results obtained by the disc diffusion method were similar. The use of moist propolis discs resulted in mean diameters of growth inhibition of 21.4 mm for H. pylori and 13.6 mm for Campylobacter spp. Dried propolis discs exhibited antibacterial effect against 73.1 % of H. pylori isolates, with a considerable zone of growth inhibition (⩾ 15 mm) in 36.4 % of isolates. Using dried propolis discs resulted in mean diameters of growth inhibition of 12.4 mm for H. pylori and 11.6 mm for Campylobacter spp. In conclusion, Bulgarian propolis possesses considerable antibacterial activity against H. pylori, and can also inhibit the growth of Campylobacter jejuni and Campylobacter coli. The potential of propolis in the prevention or treatment of H. pylori infection is worth further extensive evaluation.